PEMAHAMAN MASYARAKAT DESA PERERENAN, KECAMATAN MENGWI, KABUPATEN BADUNG, BALI TENTANG BOREH-ANGET - Titien Siwi Hartayu; Ketut Ary Widiasih (Sanata Dharma University, 2012)
Abstract : Boreh-anget is one of Bali traditional medicines used by the ancient people ofBali to warm their body and it is believed that Boreh-anget could be used for pain relieves,improving blood circulation reduces rheumatic pain, and fever. This study is aimed to identifyknowledge of recent generation in Bali about Boreh-anget, including what are the ingredientsof it, how to make it, how to use it, and what benefit by using it. This study was conducted atPererenan village, Mengwi, Badung Bali where is most all of people there using Boreh-anget.This study is non-experimental, descriptive qualitative approach, using purposive sampling.There are 78 participants with age ranging form 26 60 years old involve in this study. Dataare collected using questionnaires and supported by in-depth interview among a viewparticipants, and then the data are analyzed using enumerative methods. Results of the studyshow that 76.3% of participants knew about the ingredients of Boreh-anget, 92.6% ofparticipants knew how to make Boreh Anget, 80.3% of participants knew how to use Borehanget and 78.0% of participants knew the benefit of using Boreh-anget. Conclusions of thisstudy is that recent generation in Pererenan, Mengwi, Badung, Bali still have a high level ofknowledge about Boreh-anget.Keyword: Boreh-anget, tradisional-medicines, Bali, traditional ingredient